Urgensi Pendidikan Multikultur untuk Menumbuhkan Nilai Toleransi Agama di Indonesia - Prasetiawati, Eka (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2017)
Indonesia has a plurality of tribes and religions. The plurality of this tribe is one of the characteristics of Indonesian society that can be proud. However, we do not realize that the plurality also holds the potential for conflict that can threaten the life of the nation and the state. This has been proven in some areas of Indonesia such as the Sampit conflict between the Madurese and Dayaks, in Poso between Christians and Muslims, in Aceh between GAM and RI, the Ahmadiyah conflict, religious blasphemy, the infiltration of radicalism and terrorism, HTI dissolution etc. To minimize this, in schools must be instilled togetherness values, tolerant and able to adapt in various differences. The purpose of this study is to determine the urgency of multicultural education in Indonesia. With multicultural education, it is hoped to build multicultural discourse among teachers and students that not only able to build students' skills on subjects taught but be able to apply the values of pluralism, humanism and democracy directly in schools so that the nation is able to face various forms of conflict social. This research method is literature study (Library Research). In the approach using normative descriptive with more emphasis on the power of data analysis on existing data sources. The method uses content analysis is a method that prioritizes on the disclose aspects of the content (essence) of some existing proportions. From the results of this study, the authors conclude that the urgency of multicultural education in Indonesia is as an alternative means of solving conflicts, fostering students not deprived of cultural roots, as the foundation for the development of the national curriculum, and the realization of a multicultural Indonesian society. The implementation of the school, in the context of learning needs integrative learning model approach (teachers organize the material by linking several themes from various relevant subjects eg through religious subjects and civics), teachers have relevant learning strategy that is student centered instruction through discussion, simulation and games, strengthening character education in schools such as religious, nationalist, independent, mutual cooperation and integrity, growing religious tolerance values by schools must prepare a curriculum that includes the values of pluralism and tolerance